Conformidad hacia la educación física en estudiantes de educación secundaria de la Institución Educativa Generalísimo Don José de San Martín Nº 60052, Punchana 2022 - Heigen Vasquez, Jenrry Giovano (2025)
The general objective of the research was to describe the degree of compliance towards physical education in secondary education students of the Generalísimo don José de San Martin educational institution Nº 60052 in the Punchana district during 2022. For this reason, the type of research was used descriptive, with a univariate, cross-sectional and field design, to obtain the information, the survey technique was applied through a questionnaire, which was subjected to expert judgment. The students of the educational institution were the population and sample of the present study. The analysis of the results on the general objective shows that the degree of conformity towards physical education in the 150 (100.0%) high school students of the public educational institution for minors Generalísimo San Martín in the district of Punchana in the year 2022, is that 4.0% (n=6) are not at all satisfied, 89.3 (n=134) are not very satisfied, while only 6.7% (n=10) are very satisfied with the area of physical education.